Synthesis and biological evaluations of pyrazolo[3,4-d] pyrimidines as cyclin-dependent kinase 2 inhibitors - Kim, DC; Lee, YR; Yang, BS; Shin, KJ; Kim, DJ; Chung, BY; Yoo, KH (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2003)
A series of 1,4,6-trisubstituted pyrazolo[3,4-d]pyrimidines 15-19, 30-38 capable of selectively inhibiting CDK2 activity were synthesized by derivatization at C-4, C-6 and N-1 with various amines and lower alkyl groups. For above synthetic compounds, biological evaluation was carried out and structure-activity relationship was examined. In our series, 4-anilino compounds exhibited better CDK2 inhibitory activity and antitumor activity compared to 4-benzyl compounds. The compounds 33a,b having a 3-fluoroaniline group at C-4 showed comparable or superior CDK2 inhibitory activity to those of olomoucine and roscovitine as reference compounds. In general, the unsubstituted compounds (30a,b, 33a,b, 36a,b) at N-1 possessed higher potency than the substituted compounds (32a,b, 34a,b) for the CDK2 inhibitory activity. As for EGFR inhibitory activity, most compounds didnot have a significant activity. The compounds 32a,b exhibited potent cell growth inhibitory activity against human cancer cell lines, but their CDK2 inhibitory activities were slightly poorer than olomoucine. (C) 2003 Editions scientifiques et medicales Elsevier SAS. All rights reserved.
Keywords: CYCLIN-DEPENDENT KINASES; CHEMICAL INHIBITORS; PURINE DERIVATIVES; BINDING-SITE; POTENT; OLOMOUCINE; LIBRARIES; ANALOGS; CDK2; ATP